PROMOSI EKSPOR INDONESIA DALAM UPAYA PENINGKATAN EKSPOR KOPI KE AMERIKA SERIKAT PERIODE 2017-2020 - Muhammad Ivan Adriansyah (Jurusan Ilmu Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Sriwijaya, 2022)
This study will discuss the economic diplomacy pursued by Indonesia through its export promotion strategy to increase its coffee exports in the United States. The results of Indonesia's economic diplomacy show a positive impact, although it does not have a direct impact on export numbers. Indonesian coffee industry has to develop to meet the standards of international coffee market demands, and also have to increase the rate of coffee productions productivity in order to be able to compete with the other competitors. Economic diplomacy through export promotion is just one of many factors that could help boost Indonesian coffee export figures to the United States in the next period.